Europe - Vanden Branden, Claire (2019)
This book introduces readers to the climate, landforms, plants, animals, and people of Europe
Includes index
ages 4-8
Keywords: Continents -- Juvenile literature; Geography -- Juvenile literature; Europe -- Juvenile literature; Nonfiction